Enhancing the functionality of environmental flows through an understanding of biophysical processes in the riverine landscape - Yarnell, Sarah M.; Thoms, Martin (Frontiers in Environmental Science, 2022)
While water resource managers and river scientists recognize the inherent interconnections among river structure, physical processes, and ecological patterns, management of environmental flows remains focused on flow volumes. Implementation of more natural flow regimes has improved habitat conditions for native species in many moderately impaired rivers, but mimicking a natural flow regime in heavily modified riverine landscapes cannot be expected to yield successful ecological outcomes unless such flows trigger functional processes. For example, the restoration of peak flows will not regenerate habitats if the river is starved of sediment or if the river channel is highly confined. High biodiversity is supported when variable flow regimes interact with spatially variable (heterogeneous) river channel and floodplain forms. In contrast, as rivers become homogeneous, biodiversity decreases when these dynamic spatiotemporal interactions are limited by flow alterations, blocked by channel levees, or perturbed by sediment deficit or surplus. Thus, the design of a more natural environmental flow regime without consideration of the implications for sediment transport and implicit recognition of channel–floodplain geomorphology is likely to have limited success in river management and restoration. To enhance the functionality of environmental flows, considerations of physical, biogeochemical, and ecological processes and the inherent heterogeneity of the riverine landscape must be included. A Functional Flows approach enhances the benefits from limited environmental flow allocations by focusing on the ecological and geomorphological functionality of particular aspects of the flow regime, considering geomorphic context, and emphasizing spatiotemporal diversity at key locations in the riverscape, such as adjacent floodplains or tributary junctions. In this paper, we outline and illustrate the concept of Functional Flows using a flow-chain model and provide two case study examples from Australia and the USA, where improvements in channel habitat and reconnection with the floodplain help to achieve the desired functionality of environmental flows.